Underground Space Ownership in Malaysia : Defining the Rights - Farah, Zaini; Aminah, Mohsin (Human Resource Management Academic Research Society, 2021)
Underground space development is one of the development alternatives taken by many countries including Malaysia. Therefore, the National Land Code 1965 (NLC 1965) was amended to insert Part Five (A) for underground space disposal. However, the legislation is still ambiguous and has raised many arguments between the landowners and the developers. Land ownership has become the major issues in developing the underground space. It creates conflicts when underground space to be developed by the different landowners on the surface. Even though the legislation is there, the mechanism of implementation is absent. Hence, this study was undertaken to understand the concept of surface landowner towards his underground space and underground space ownership. This study is a purely qualitative study and interviews were conducted with four selected respondents who were involved in underground space development in Malaysia by using the semi-structured interview questions to get their views and opinions to support this study. The obtained data were then analyzed descriptively. The findings have shown that two important elements need to be emphasized in underground space ownership, which is the land rights and depth. However, to further assist the underground space development in the future, Malaysia must consider revising the concept of underground space tenure to help in explaining and differentiate the tenure and rights held by the surface landowner, the underground space owner and also the developer individually.